2018
DOI: 10.1096/fj.201701041rrr
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid antagonist mifepristone attenuates sound‐induced long‐term deficits in auditory nerve response and central auditory processing in female rats

Abstract: Systemic corticosteroids have been the mainstay of treatment for various hearing disorders for more than 30 yr. Accordingly, numerous studies have described glucocorticoids (GCs) and stressors to be protective in the auditory organ against damage associated with a variety of health conditions, including noise exposure. Conversely, stressors are also predictive risk factors for hearing disorders. How both of these contrasting stress actions are linked has remained elusive. Here, we demonstrate that higher corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Likewise, elevated cortisol levels influence IHC synapses contacting postsynaptic auditory fibers as well as sound responses of afferent auditory fibers (Singer et al, 2013 ). Additionally, an acute behavioral stress paradigm and glucocorticoid receptor antagonists influence sound-induced suprathreshold auditory nerve responses, indicating that circulating cortisol reaches the cochlea via the bloodstream (Singer et al, 2013 , 2018 ). Moreover, the same behavioral stress paradigm triggered sound-enrichment driven elevated levels of the LTP-associated activity-regulated cytoskeletal protein (Arc) in the hippocampus (Singer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, elevated cortisol levels influence IHC synapses contacting postsynaptic auditory fibers as well as sound responses of afferent auditory fibers (Singer et al, 2013 ). Additionally, an acute behavioral stress paradigm and glucocorticoid receptor antagonists influence sound-induced suprathreshold auditory nerve responses, indicating that circulating cortisol reaches the cochlea via the bloodstream (Singer et al, 2013 , 2018 ). Moreover, the same behavioral stress paradigm triggered sound-enrichment driven elevated levels of the LTP-associated activity-regulated cytoskeletal protein (Arc) in the hippocampus (Singer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments demonstrated that exposures to defined enriching, mild traumatic, or severe traumatic sound pressure levels (SPL) caused long-lasting alterations to sound-sensitivity and differentially induced hippocampal plasticity (Singer et al, 2013 ). Likewise, acoustically induced differences in central sound sensitivity correlated with sensitivity to stress as shown through a social stress paradigm or pharmacological inhibition of stress receptors (Singer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To shed more light on this existing inconsistency, we performed a multimodal dataset analysis of participants with tinnitus and volunteers without tinnitus. Aiming to maximize information about auditory-specific changes in tinnitus, the study design aligned with several a priori assumptions (i) we focused on mild hearing-impaired volunteers and participants with tinnitus with hearing thresholds <40 dB in order to obtain homogenous groups ( Knipper et al, 2013 ; Shore et al, 2016 ); (ii) we excluded participants with co-occurrences of tinnitus and hyperacusis which may disturb interference through dissimilar central neural responses ( Gu et al, 2010 ; Song et al, 2014 ); (iii) as hearing-impaired matched rats with and without tinnitus have been shown to differ in terms of the size of suprathreshold central auditory brainstem response (ABR) waves independent of hearing thresholds ( Rüttiger et al, 2013a ), we included detection of suprathreshold ABR waves; (iv) As the sound-induced (ABR) wave size (wave amplitude) reflects synchronized neural activity ( Johnson and Kiang, 1976 ; Ruttiger et al, 2017 ), we included BOLD fMRI activity, which is known to change in response to a task requiring elevated local metabolism ( Logothetis et al, 2001 ); (v) as an increased level of evoked BOLD fMRI activity has been previously linked to more synchronous fMRI correlations at rest ( Haag et al, 2015 ), we hoped to strengthen the obtained findings through additional analyses of resting-state functional connectivity MRI (r-fcMRI) in anatomically predefined auditory pathway and connected regions; and (vi) finally, the accepted influence of corticosterone levels on early and late ABR waves after tinnitus-inducing trauma ( Singer et al, 2018 ; Singer et al, 2013a ) and the positive association between glucocorticoid resistance and tinnitus ( Hébert et al, 2012 ; Mazurek et al, 2012 ), motivated us to analyze the cortisol levels of each participant.…”
Section: Introductionmentioning
confidence: 86%
“…Suppression of inflammatory pathways may trigger compensatory responses by activation of alternative pathways (22) since inflammation is a necessary reaction protecting the organ from excessive damage (22). Also, there is increasing evidence that excessive activation of the glucocorticoid pathway can be neurotoxic (2326). Alternative therapeutic interventions should, therefore, aim at stabilizing the local cochlear environment by balancing endogenous pro- and anti-inflammatory reactions, thus, allowing full resolution of inflammation and recovery of organ homeostasis that results in preservation of residual organ structures and improved speech perception (1).…”
Section: Introductionmentioning
confidence: 99%